Pengaruh Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing pada Materi Kelarutan dan Hasil Kali Kelarutan terhadap Hasil Belajar Peserta Didik Kelas XI MIPA MAN 2 Padang - Ridho Abdul Aziz, Iryani, Mawardi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The usage of appropriate teaching material can help student achieve learningobjectives by motivate and attract student interest in order for them to study actively inlearning process. One of the teaching material that can be used to support the learningprocess according to the 2013 curriculum is teaching materials in the form of GuidedInquiry Based Student’s Worksheets. This research aims to determine the effect ofstudent’s worksheet based on guided inquiry for solubility and solubility productconstant toward 11th grade senior high school student’s study result. The research typewas quasi experiment research which used non-equivalent control group design. Thepopulation was all 11th grade senior high school students from MAN 2 Padang on2017/2018 academic year. The research sample was chosen using purposive samplingtechnique which resulted XI MIPA 3 as the experiment class and XI MIPA 5 as thecontrol class. The research instrument was study test result in form of multiple choice,which consists of pre-test and post-test. Based on this research, the N-gain pointobtained in this experiment class was 0.68 which considered medium and in the controlclass was 0.55 which considered medium. The result based on the data analysis wasboth sample class distributed normally and has homogeneous variance. Based on the ttesttoward significant standard 0.05 resulted that tcount (4.21) > ttable (1.67). This resultshowed that the increasing of student’s study result from experiment class was higherthan control class significantly. It can be concluded that the usage of student’sworksheet on solubility and solubility product constant take effect and can be used toincrease 11th grade senior high school student’s study result.Keywords:effect, student’s worksheet, guided inquiry, solubility and solubility productconstant, study result